Efeitos do açafrão (Curcuma longa L.) em frangos de corte inoculados experimentalmente com Salmonella Typhimurium - Nascimento, Gisele Mendanha (2016)
It was aimed to evaluate the effects of different doses of Curcuma longa in Salmonella Typhimurium control on performance, intestinal integrity, fecal excretion of Salmonella, lymphocyte count in secondary lymphoid organs, histopathology, biochemical profile and Salmonella research in organs of experimentally inoculated broilers. A total of 672 male chicks were distributed in a completely randomized design, in a 4 x 2 factorial arrangement (doses of Curcuma longa x inoculation with Salmonella Typhimurium), distributed in eight treatments and six replications. The birds were orally inoculated, on the first day of age, with 0.5 ml of buffered saline solution containing 1.2 x 104 CFU/mL of Salmonella Typhimurium. Treatment 1 consisted in the control group, with no addition of Curcuma longa and no inoculation of Salmonella typhimurium; treatments 2, 3 and 4 consisted in the groups receiving Curcuma longa at doses of 1%, 2% and 3% in the feed, respectively. Treatment 5 is the group which received only Salmonella Typhimurium inoculation; treatments 6, 7 and 8 received Curcuma longa at doses of 1%, 2% and 3% in the feed, respectively, besides inoculation of Salmonella typhimurium in the crop. It was noted statistical difference in performance, with better results in birds supplemented with 1% of Curcuma longa, and not inoculated with Salmonella Typhimurium, since the regression analysis of the final weight and weight gain showed the best dose for the two variables was 0.82%. At 21 days old, the regression showed a linear effect on weight gain and feed intake. At 35 days old, the regression showed a quadratic effect for weight gain and feed intake. The dose of 1% turmeric prevented intestinal colonization by Salmonella.Dosage and inoculation also influenced the histomorphometry and the pH of the intestinal segments. It was found, at seven days, Salmonella was isolated from the liver of birds in the control group and birds in the group treated with 1% of Curcuma longa. Salmonella Typhimurium was not isolated in the spleen, in any of the studied ages. At seven, 21 and 35 days old, birds orally inoculated with Salmonella Typhimurium had higher lymphocyte counts in the spleen when compared to not inoculated birds. There was no significant difference in histopathological evaluations of liver, kidney, and cecal tonsils. At 21 days old, there was a higher frequency of mucous in the duodenum of birds supplemented with 1 and 3% of turmeric. It was found in biochemical profile, at 14 days old, changes in levels of aspartate aminotransferase (AST), cholesterol and triglycerides, and regression analysis showed a linear effect for creatinine and aspartate aminotransferase (AST). At 36 days old, in glucose levels, uric acid, aspartate aminotransferase (AST), gamma glutamyl transferase (GGT), total protein and globulin, regression analysis showed a linear effect for total protein and globulin, and quadratic effect for uric acid. In conclusion, the inclusion of 1% of Curcuma longa in the feed improves the final weight, weight gain, feed intake and feed conversion, as well as inhibited the intestinal colonization of Salmonella Typhimurium and preserved intestinal integrity. The inclusion of 1% has also altered the biochemical profile, with a reduction in cholesterol levels.